Modelling the effect of macro-segregation on the fracture toughness of heavy forgings using FFT based crystal plasticity simulations. (September 2022) - Ren, S.C.; Marini, B.; Forget, P.
Abstract: The local approach has been successful in evaluating the brittle fracture probability of nuclear pressure vessel steels by establishing a link between microstructural defects and the macroscopic fracture behaviour. The evaluation of fracture probabilities relies on the applied stress on the smallest representative elementary volume. A proper description of the stress heterogeneities in polycrystals helps refine the prediction. The current work investigates the effect of carbon macro-segregation in heavy forgings and demonstrates a workflow combining crystal plasticity with the Microstructure Informed Brittle Fracture (MIBF) local approach model in fracture toughness prediction. The microstructural and mechanical properties of low alloy steels with different segregation levels were evaluated. A dislocation-density based crystal plasticity model which contains carbide strengthening contribution was identified and applied for modelling microstructure influence on local stress distributions. Results show that the microstructural evolution observed at high carbon levels has a significant influence on local stress distributions, which in turn affects the fracture toughness. The simulation results also demonstrate that, with proper input of microstructural information, the MIBF model is capable to predict the shift of the brittle-to-ductile transition zone with the variation of carbon and alloying elements and gives insights about factors affecting the resistance of materials. Highlights: Investigation of macro-segregation effects in synthetic alloys. Mechanical properties and microstructures affected by carbon/alloy element contents. Workflow for predicting fracture toughness with crystal plasticity and MIBF model. Modelling of fracture toughness evolutions at different carbon contents.